2022
DOI: 10.1590/0037-8682-0657-2021
|View full text |Cite
|
Sign up to set email alerts
|

The health-related quality of life in patients with Chagas disease: the state of the art

Abstract: Chagas disease (CD) is a neglected tropical disease associated with poverty in which patients are surrounded by stigma. These factors can contribute to reducing health-related quality of life (HRQoL). Therefore, a broad discussion of HRQoL in the CD population is required. This study aimed to discuss the main findings of HRQoL in patients with CD, focusing on the association between sociodemographic and lifestyle factors, echocardiographic and functional determinants, and the effect of non-invasive interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
12

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 60 publications
1
12
0
12
Order By: Relevance
“…In the present study, the MLwHFQ score correlated with almost all SF-36 domains. The SF-36 is the most used questionnaire in patients with Chagas disease [7]. Therefore, the present study demonstrated a high correlation between both questionnaires.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the present study, the MLwHFQ score correlated with almost all SF-36 domains. The SF-36 is the most used questionnaire in patients with Chagas disease [7]. Therefore, the present study demonstrated a high correlation between both questionnaires.…”
Section: Discussionsupporting
confidence: 67%
“…Structural and functional abnormalities, associated with stigma and fear of sudden death, can compromise the health-related quality of life (HRQoL) of these patients [7][8][9][10]. However, the assessment of HRQoL remains controversial, since there are no specific questionnaires for patients with Chagas disease, and it is usually evaluated using generic questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…Variation of VO 2peak during the follow‐up period was used as a measure of effect (clinical outcome) due to its significant prognostic value, whose increase of 1 ml kg −1 min −1 is associated with an approximate 10% reduction in the risk of death [19]. Moreover, VO 2peak is also associated with patient‐reported outcomes, including health‐related quality of life [16]. VO 2peak was measured by CPET on a treadmill (Inbramed, Brazil), using a ramp protocol, being considered the maximum value achieved 60 s before or after the peak workload.…”
Section: Methodsmentioning
confidence: 99%
“…Considering increased functional capacity is positively associated with quality of life and that CR programs may improve functional capacity and health‐related quality of life of patients with CCC [16], whose treatment costs are usually high in the context of scarce resources, studies evaluating the cost‐effectiveness of CR programs designed for CCC patients are required for better allocation of healthcare resources. Therefore, the present study aimed to perform an economic evaluation of a CR program designed for patients with CCC, considering the overall healthcare costs and the cost‐effectiveness evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of CD, many studies have quantitatively evaluated the HRQoL of patients [9][10][11][12][13] . A recent state-of-the-art study 14 summarized the current findings and postulated that HRQoL is worse in patients with CD compared with that in healthy individuals. Moreover, HRQoL is more compromised in women with cardiovascular and gastrointestinal symptoms among patients with worse functional class, lower levels of physical activity, and worse cardiac function.…”
Section: Introductionmentioning
confidence: 99%